2021
DOI: 10.31224/osf.io/a3ntv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generalized Chemical Equilibrium Constant of Formaldehyde Oligomerization

Abstract: Formaldehyde reacts with solvents that contain hydroxyl groups (R–OH) in oligomerization reactions to oxymethylene oligomers (R–(OCH2)n–OH). The chemical equilibria of these reactions have been studied in the literature for water, for the mono-alcohols methanol, ethanol, and 1-butanol, as well as for the diols ethylene glycol and 1,4-butynediol. In the present work, the collective data were analyzed. It was found that the prolongation of the oxymethylene chains by the addition of formaldehyde can be described … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…They found that the chemical equilibria of the reactions leading to formaldehyde oligomers with a minimum of two CH 2 O segments, for example reactions (II) and (IV) of this work, can be described using a generalized mole fraction-based chemical equilibrium constant that is scribed very well. This shows that the generalized mole fraction-based chemical equilibrium constant from Kircher et al 29 for the oligomerization reactions of formaldehyde, leading to oligomers with a minimum of two CH 2 O segments, also holds for isoprenol. The result for K x,(III) fits perfectly in the trend observed by Kircher et al 29 for the other alcohols, see The bars are labeled with the respective alcohol.…”
Section: Chemical Equilibriamentioning
confidence: 58%
See 4 more Smart Citations
“…They found that the chemical equilibria of the reactions leading to formaldehyde oligomers with a minimum of two CH 2 O segments, for example reactions (II) and (IV) of this work, can be described using a generalized mole fraction-based chemical equilibrium constant that is scribed very well. This shows that the generalized mole fraction-based chemical equilibrium constant from Kircher et al 29 for the oligomerization reactions of formaldehyde, leading to oligomers with a minimum of two CH 2 O segments, also holds for isoprenol. The result for K x,(III) fits perfectly in the trend observed by Kircher et al 29 for the other alcohols, see The bars are labeled with the respective alcohol.…”
Section: Chemical Equilibriamentioning
confidence: 58%
“…Note that the peaks of MG 2 1¦ and MG 2 2¦ were always superimposed in the spectra due to the symmetry of the molecule. Following Kircher et al, 29 the approach was validated in preliminary experiments with gravimetrically prepared samples of (isoprenol + methylal) by comparison of the gravimetrically and the NMR-spectroscopically determined mole fraction of methylal.…”
Section: Quantitative Evaluation Of 13 C-nmr Spectramentioning
confidence: 99%
See 3 more Smart Citations